A cost analysis study for lifelong learning program organized by community college - Md Shariff, Noorul 'Ain; Abdul Kadir, Suhaida; Idris, Khairuddin; Basri, Ramli (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This study aimed to compare cost of lifelong learning program particularly for Kluster Jahitan dan Pakaian at three community colleges that represent three zones in Malaysia. This study only discusses the cost of programs run by community colleges in 2014 until 2016. The cost-effectiveness analysis methods were used to achieve the objectives of the study. The results found that community colleges spend 56% of the total cost in personnel costs, 43% on the cost of equipment and only 1% of the cost of materials. The financial analysis cost showed that there is a difference among community colleges.